ICT for curriculum enhancement - Monteith, Moira (Intellect, 2004)
This book considers the cognitive nature of courses connected with ICT or using ICT as an integral part of the course, including some views on the associated learning and teaching styles. Which factors lead to learning outcomes and are these intended or fortuitous? Factors may include ones specific to particular subject areas and their relationship with ICT, motivation associated with ICT usage, the interest which teachers, pupils and students who enjoy using ICT bring to the learning context. R.